Faktor-faktor Penyebab Prokrastinasi Akademik Peserta Didik dan Implikasinya dalam Pelayanan BK - Dewi, Anggita Purnama; Suhaili, Neviyarni (Lembaga Yasin AlSys, 2025)
This research is motivated by the phenomenon of the condition of academic procrastination from students which is classified as high seen from the symptoms that appear such as dislike for certain teachers causing neglect of learning tasks, wasting time chatting, watching television, watching in the cinema and so on, and having difficulty in preparing physical and psychological conditions so that when attending lessons are in a lackluster condition. The objectives of this study are (1) to describe the factors that cause students' academic procrastination at SMKN 2 Padang, (2) to describe the internal factors that cause students' academic procrastination at SMKN 2 Padang, and (3) to describe the external factors that cause students' academic procrastination at SMKN 2 Padang. This type of research is quantitative research with a descriptive approach. The population of this study amounted to 425 students of SMK N 2 Padang who were enrolled in the 2024/2025 school year, with a sample size of 206 students. Sample selection using proportional ramdom sampling technique. The data collection technique used an academic procrastination scale. Data were analyzed using descriptive techniques. The results of this study reveal that the factors that cause students' academic procrastination at SMK N 2 Padang are seen from: (1) physical condition factors are generally in the high category, (2) psychological condition factors are generally in the medium category, (3) family condition factors are generally in the high category, (4) school environment factors are generally in the high category, and (5) community environment factors are generally in the high category. Based on the findings of this study, it is expected that counseling teachers can provide services to avoid students' academic procrastination.